(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study examines digital governance in addressing the misuse of Digital Population Identity (IKD) services at the Population and Civil Registration Office (Disdukcapil) of Makassar City. The rapid digitalization of public services, including IKD, has improved administrative efficiency but also introduced new risks, particularly misuse and digital fraud. This research aims to analyze how digital governance is implemented in mitigating such risks. The study employs a descriptive qualitative approach using the information ecology framework proposed by Bekkers and Homburg (2005), which includes four dimensions: institutional arrangements, information relations, technical infrastructure, and monitoring and control. Data were collected through in-depth interviews with Disdukcapil officials and citizens affected by IKD misuse, as well as observation and documentation. The findings reveal that digital governance practices are primarily administrative, focusing on formal procedures, controlled service access, complaint recording, and basic public education. However, limitations persist in terms of centralized authority, uneven information dissemination, limited digital literacy, and reactive monitoring mechanisms. These conditions reduce the effectiveness of efforts to prevent misuse, especially those driven by social engineering practices. This study concludes that strengthening digital governance requires improved cross-sector coordination, more adaptive and participatory communication strategies, enhanced digital literacy, and the development of risk-based monitoring systems to effectively mitigate misuse in digital public services.